Preparing Educators for Inclusive Bilingual Education: A Boundary Crossing Laboratory Between Professional Groups - Martínez-Álvarez P. (Moscow State University of Psychology and Education, 2021)
Teacher education programs prepare candidates for bilingual, English as a second language, or special ed¬ucation as separate professionals. This creates challenges when teaching bilingual children with disabilities. There is a need to cross boundaries combining expertise and preparing teachers for children’s uniqueness. Re¬sponding to this need, the researchers organized a change laboratory with 14 professors and two State Depart¬ment of Education consultants. The study explored boundary expressions and their relationship to the larger activity. It also looked at the learning that took place during boundary crossing efforts. Boundaries were identi¬fied around bilingual teacher preparation, cross-disciplinary programmatic, and paradigmatic aspects. While boundary crossing at the intrapersonal level and at the interpersonal level were important, the need to engage multiple institutions was centered. In addition, the discussion manifested that for inclusive bilingual education teacher preparation, there was a need to go beyond the institutional level to reach to policy makers and address the sociopolitical resistance against bilingual education. Throughout the study, participants engaged primarily in the epistemic learning actions of analyzing and modeling. Through volitional actions, the participants real¬ized a renewed object for their activity. This study widens the understanding of possibilities for taking shared educational responsibility through boundary crossing between professionals in preparation programs.